1992
DOI: 10.1002/hfm.4530020104
|View full text |Cite
|
Sign up to set email alerts
|

Ergonomic challenges in conventional and advanced apparel manufacturing

Abstract: Apparel manufacturing is a labor‐intensive, assembly‐line process requiring significant amounts of repetitive, skilled manipulation. A survey of three typical plants in the southeastern United States identified relatively high frequencies of musculoskeletal discomfort among the sewing operators. Poorly designed and maladjusted workstations contributed to these reported problems. Subsequent research found that ergonomic interventions including redesign and proper adjustment of workstations, use of ergonomically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…Bao et al (1996) and Galka (1991) used a design with a post-test only and a comparison group. Kelly et al (1992) reported on several small studies in their article with varying designs. Rowe (1987) used a non-traditiona l design comparing groups of individuals with repetitive strain injuries at diVerent periods after the intervention, and Yamada et al (1993) did not provide su cient information to determine the design.…”
Section: Multiple Component Studiesmentioning
confidence: 96%
“…Bao et al (1996) and Galka (1991) used a design with a post-test only and a comparison group. Kelly et al (1992) reported on several small studies in their article with varying designs. Rowe (1987) used a non-traditiona l design comparing groups of individuals with repetitive strain injuries at diVerent periods after the intervention, and Yamada et al (1993) did not provide su cient information to determine the design.…”
Section: Multiple Component Studiesmentioning
confidence: 96%
“…Several studies examined musculoskeletal disorders associated with sewing operator^.'^.'^. '^^'^ o ther studies have focused on evaluating sittinglstanding postures, chair designs, workstation design, and the use of specialized sewing equip-Kelly et al 24 conducted research in three apparel manufacturing plants in the southeastern United States. Data included observations, anthropometric measurements, and interviews with operators.…”
Section: Review Of Related Researchmentioning
confidence: 99%
“…The development of musculoskeletal diseases as a result of poor postures, poorly designed and maladjusted workstations, and lack of awareness about the potential benefit of ergonomics have been widely reported (Kelly et al ., 1992; Parimalam et al ., 2006). Studies of the work practices of machine operators, both in the developed and some developing countries, have consistently shown that ergonomically appropriate sewing workstations are needed if sewing machine operators are to perform their tasks comfortably and efficiently (Yu and Keyserling, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…They were lack of worker selection and lack of appropriate training to prevent occupational hazards or work‐related diseases, the poor ergonomic design of the work place and task including work organization, poor working postures, lack of task variation and insufficient rest breaks. Ergonomic interventions including the redesign and proper adjustment of workstations, use of ergonomically designed seating, and training in low‐risk methods and postures substantially reduce these complaints (Kelly et al ., 1992; Kawakami and Kogi, 2005). A healthy and safe work environment therefore helps reduce costs associated with absenteeism and the loss of skilled staff while increasing staff morale, job enrichment and quality of work life.…”
Section: Introductionmentioning
confidence: 99%